Mekanisme Ganti Kerugian Terhadap Korban Tindak Pidana Dalam Perkara Penganiayaan Di Kota Surakarta - Husein, Husein, Hartanto, S.H. M.Hum (2016)
Crime is an integral part of human life on earth. The crimesare common and familiar in the community is that a criminal act persecution. However, in practice, laws are prioritizing the rights of the suspect or the accused, while the victims' rights are ignored. One of rights is rightfully of victims is penalized restitution. Restitusion for victims of crime can basically be done in three ways, that is through: 1) Merger Case of restitusion, 2) Torts lawsuits 3) Application for restitution. In practice, there are also other mechanisms through non litigation (penal mediation) between the perpetrator (suspect) with the victim in order to accelerate the victims to getrestitutionin accordance with the material losses suffered by the victim. But there are constraints in terms of the victims receive restitusionthat is the victim did not know about the the mechanism ofrestitution complex legal procedures the length of legal proceedings and still ambiguous the rule of law, about the setting restitution.